2012
DOI: 10.1002/ppap.201100140
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Functionalization of Multiwalled Carbon Nanotubes and Their Use in the Preparation of Nylon 6‐Based Nanohybrids

Abstract: The possibility to obtain carbon nanotubes (CNT)/polyamide 6 composites with excellent mechanical properties in a simple, industrially scalable way is investigated. Commercial CNTs are treated by plasma while changing some key parameters (exposure time, plasma power, type of gas) in order to optimize the process and to achieve a sufficient degree of functionalization. The treated samples are characterized by Fourier transform infrared spectroscopy, Raman spectroscopy and X‐ray photoelectron spectroscopy. The m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
40
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 59 publications
(43 citation statements)
references
References 27 publications
(61 reference statements)
3
40
0
Order By: Relevance
“…Surprisingly, the plasma functionalization causes a slight decrease of this property, despite the higher level of adhesion, dispersion and orientation achieved, as demonstrated by the above presented data. This unexpected result can be explained considering that the functionalization partially destroyed the graphenic sp 2 structure of the CNTs walls after introducing oxygen moieties as demonstrated by the increase of the ID/IG ratio as measured by Raman spectroscopy and discussed in our previous works [5,10]. Other authors [23][24][25] while studying PA12/CNT systems found some relationship between the rheological behaviour of PA12, its end groups and the electrical conductivity of the nanocomposites.…”
Section: Resultsmentioning
confidence: 89%
See 4 more Smart Citations
“…Surprisingly, the plasma functionalization causes a slight decrease of this property, despite the higher level of adhesion, dispersion and orientation achieved, as demonstrated by the above presented data. This unexpected result can be explained considering that the functionalization partially destroyed the graphenic sp 2 structure of the CNTs walls after introducing oxygen moieties as demonstrated by the increase of the ID/IG ratio as measured by Raman spectroscopy and discussed in our previous works [5,10]. Other authors [23][24][25] while studying PA12/CNT systems found some relationship between the rheological behaviour of PA12, its end groups and the electrical conductivity of the nanocomposites.…”
Section: Resultsmentioning
confidence: 89%
“…An increase of this ratio can be correlated with the degree of functionalization by the different vibration modes of carbon atoms in the presence of defects, generated during the functionalization process and associated to the presence of oxygen or other atoms in the nanotube structure. [5,17,18]. In Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations